Cu-Based Conductive MOF Grown in situ on Cu Foam as a Highly Selective and Stable Non-Enzymatic Glucose Sensor - Hu, Qin; Qin, Jie; Wang, Xiao-Feng; Ran, Guang-Ying; Wang, Qiang; Liu, Guang-Xiang; Ma, Jian-Ping; Ge, Jing-Yuan; Wang, Hai-Ying (Frontiers in Chemistry, 2021)
A nonenzymatic electrochemical sensor for glucose detection is executed by using conductive metal-organic framework (MOF) Cu-MOF, which is built from 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) ligand and copper acetate by hydrothermal reaction. The Cu-MOF demonstrates superior electrocatalytic activity for glucose oxidation under alkaline pH condition. As an excellent nonenzymatic sensor, the Cu-MOF grown on Cu foam (Cu-MOF/CF) displays an ultra-low detection limit of 0.076 μM through a wide concentration range (0.001 mM–0.95 mM), and a strong sensitivity of 30030 mA μM−1 cm−2. Overall, the Cu-MOF/CF exhibits low detection limit, high selectivity, excellent stability, fast response time and good practical application feasibility for glucose detection, and can promote the development of MOF materials in the field of electrochemical sensor.